Urban-rural and sex differentials in tuberculosis mortality in Bangladesh: results from a population-based survey - Sarker, Malabika (Tropical medicine & international health, 2019)
Objective To assess tuberculosis mortality in Bangladesh through a population-based survey using a Verbal Autopsy tool. Methods Nationwide mortality survey employing the WHO-recommended Verbal Autopsy (VA) tool, and using InsilicoVA, a data-driven method, to assign the cause of death. Using a three-stage cluster sampling method, 3997 VA interviews were conducted in both urban and rural areas of Bangladesh. Cause-specific mortality fractions (CSMF) were estimated using Bayesian probabilistic models. Results 6.8% of total deaths in the population were due to TB [95% CI: (5.1, 8.9)], comprising 12.0% [95% CI: (11.1, 12.8)] and 6.42% [95% CI: (5.4, 7.3)] of total male and female deaths, respectively. This proportion was highest among adults age 15-49 years [12.2%, 95% CI: (9.4, 14.6)]. The urban population is more likely to die from TB, and urban males have highest CSMF [13.6%, 95% CI: (9.1, 16.9)]. Conclusion Our survey results show that TB is the fifth major cause of death in the general population and that sex and place of residence (urban/rural) have a significant effect on TB mortality in Bangladesh. The underlying causes of higher rates of TB-related deaths in urban areas and particularly among urban males, who have better knowledge and higher enrollment in the DOTS Program, need to be explored.
First published: 22 October 2018
Gesehen am 20.05.2019